Cytokine-primed umbilical cord mesenchymal stem cells enhanced therapeutic effects of extracellular vesicles on osteoarthritic chondrocytes - Nguyen, Thu Huyen; Dao, Huy Hoang; Duong, Chau Minh; Nguyen, Xuan-Hung; Hoang, Diem Huong; Do, Xuan-Hai; Truong, Trung Quang; Nguyen, Tu Dac; Nguyen, Liem Thanh; Than, Uyen Thi Trang (Frontiers in Immunology, 2022)
In recent years, extracellular vesicles (EVs) secreted by mesenchymal stem cells (MSCs) have emerged as a potential cell-free therapy against osteoarthritis (OA). Thus, we investigated the therapeutic effects of EVs released by cytokine-primed umbilical cord-derived MSCs (UCMSCs) on osteoarthritic chondrocyte physiology. Priming UCMSCs individually with transforming growth factor beta (TGFβ), interferon alpha (IFNα), or tumor necrosis factor alpha (TNFα) significantly reduced the sorting of miR-181b-3p but not miR-320a-3p; two negative regulators of chondrocyte regeneration, into EVs. However, the EV treatment did not show any significant effect on chondrocyte proliferation, and TGFβ-EVs even slowed it down. Meanwhile, EVs from both non-priming and cytokine-primed UCMSCs induced migration at later time points of measurement. Moreover, TGFβ-primed UCMSCs secreted EVs that could upregulate the expression of chondrogenesis markers (COL2 and ACAN) and downregulate fibrotic markers (COL1 and RUNX2) in chondrocytes. Priming UCMSCs with cytokines can deliver selective therapeutic effects of EV treatment in OA and chondrocyte-related disorders.